Why think? : philosophical play from 3-11 - Stanley, Sara (Continuum, 2012)
We live in an ever demanding world where independent, creative thinking is highly prized. We want the children of the future to have the skills and confidence to form their own ideas, and have the confidence and resilience to speak up for what they believe in. Why Think? will enable practitioners of children aged 3-11 to confidently turn their classrooms into spaces where thinking, challenging and reasoning become as natural as play. In this book, the author of But Why? explores how to maximise philosophical play through activities, games and parental engagement. Why Think? Includes: †¢ Inspirational case studies†¢ Facilitation techniques and information on philosophical concepts†¢ A list of recommended books and resources, online quizzes, thinking games and useful web links†¢ Question-board activities to stimulate daily thinking The book is visually interesting with lots of annotated sessions, drawings, photos, and ideas for resources. A must for all early years and primary practitioners.